GAMBARAN TINGKAT KECEMASAN TENAGA KESEHATAN DALAM MENGHADAPI SITUASI PANDEMI COVID-19 DI RUANGAN ISOLASI DI RS BHAYANGKARA MANADO - Tidore, Herlice (Journal Of Community & Emergency, 2024)
Health workers as the front line in handling Covid-19 have a high risk of transmission. This can cause psychological problems in the form of anxiety. The existence of anxiety can have an impact on increasing work errors, deteriorating physical and mental conditions, decreasing work productivity, and decreasing service quality. To find out the description of the level of anxiety of health workers in dealing with the Covid-19 pandemic situation in the Isolation Room at Bhayangkara Hospital Manado This research is a quantitative study with a descriptive research design, namely the research method used with the aim of making an objective picture of a situation. The population is 32 people with the sample using the total population. the sample in this study amounted to 32 samples. The results of the study obtained the characteristics of respondents, based on age, most of them were > 30 years old as many as 21 respondents (70%). Gender is mostly female, around 19 respondents (63.3%). Most of the last education DIII about 15 respondents (50%). And most of the jobs are nurses totaling 28 respondents (93.3%). The results showed that the highest level of anxiety of respondents was moderate anxiety, amounting to 17 respondents (56.7%) and followed by mild anxiety, amounting to 10 respondents (33.3). The conclusion of this study is that most health workers experience mild and moderate anxiety.